The promotion of women and girls in Swiss sports associations: Addressing, launching, and implementing decision-making structures and promotion programmes - Sarah Vögtli; Matthias Buser; Siegfried Nagel (Bern Open Publishing, 2023)
Many historically male-dominated sports still have a lower participation of women and girls at all levels. Women also seldom occupy decision-making positions at both association and club levels. At the same time, associations and sponsors increasingly advance civil society obligations to promote the participation and integration of women and girls in sport. Sport federations with relatively low female athlete participation are becoming proactive in this area, however, they depend on the cooperation of member clubs to promote integration. There are a variety of starting points of a commitment to promotion, which raises the question as to how the promotion of women and girls moves on a federation agenda and then further into the operational area. Against a background of launching and implementation, the extent to which sports federations trigger control impulses and initiate programmes, is also relevant, as is how the clubs organise local and club-specific implementation. This study uses qualitative case studies to examine federation policy processes and the structural anchoring of the promotion of women and girls, as well as specific promotion programmes and measures. In three selected Swiss sports federations, ten problem-centred interviews with decision-makers and six focus groups with club representatives were used to trace various phases of the promotion of women and girls. The policy analysis procedure is based on the phases of the policy cycle - a simplified representation of programme development and implementation - and draws on differentiated explanatory approaches (Campbell, 2004; Enjolras & Waldahl, 2007; Kingdon, 1995). Qualitative summary content analysis was used for the analysis. The research shows that functions and offices at the federation level are held by women, but that decision-making influence is not ensured overall. An interesting observation includes the process of outsourcing a "women's sport department" in two federations. While this generates more visibility, it can also create challenges in clarifying responsibilities if other departments are sufficiently sensitised to the issues. In addition, specific bodies for the promotion of women and girls should be provided with sufficient financial and human resources to have impact beyond visibility. The redistribution of resources thus becomes a barrier to the effective interpretation of funding commitments. In particular, the (partial) financing of funding projects by external actors seems to motivate associations towards implementation. It should be noted that committed actors at both federation and club levels are key drivers of development of the promotion of women and girls in sport. Other important drivers are sport policy and societal expectations and demands. This applies both to the structural anchoring in federations and the local implementation in clubs, which are in many cases already committed organisations. In summary, external pressures, steering impulses and organisational goals are conditions for the successful promotion of women and girls in organised sport. Campbell, J. L. (2004). Institutional Change and Globalization. Princeton University Press. Enjolras, B., & Waldahl, R. (2007). Policy-making in sport: The Norwegian case. International Review for the Sociology of Sport 42(2), 201-216. https://doi.org/10.1177/1012690207084753 Kingdon, J. (1995). Agendas, Alternatives and Public Policy (2nd ed.). Little Brown.